Recent advances in II-IV group semiconductor and carbon-based quantum dots for fluorescence based sensing of metal ions in water - Das, Sohel (Environmental Science Nano, 2023)
Quantum dots (QDs), which are commonly considered semiconductor nanoparticles with a size of <10 nm, have recently emerged as an intriguing field in materials science due to their unique size-dependent optical and electronic properties, chemical stability, and considerable potential for a wide range of applications. To date, new strategies and technologies are being developed for the application of QDs as optical sensors for measuring toxic metal ions in the aquatic environment owing to their properties of high sensitivity, low preparation cost, and portability. In this review, we discuss recent scientific developments based on the optical sensing of metal ions in the aquatic environment by QDs, especially focusing on II–VI group semiconductor QDs and carbon-based QDs. This review is subdivided into sections focusing on the various types of detection mechanisms, which are primarily based on the quenching or enhancement of the fluorescence of QDs. Furthermore, design strategies, such as quenching by direct analyte attachment to QDs, imperfections on the QD surface, and interruption in fluorescence resonance energy transfer (FRET) in the presence of analyte, are discussed. To provide insights into recent progress on QD (II–VI group QDs and carbon QDs)-based optical sensing, we compiled two comprehensive tables comparing QDs and their detection mechanisms and detection range. Finally, we discuss the future prospective of the present sensing strategies.
uGDX
Keywords: NATURAL SCIENCES::Chemistry::Theoretical chemistry::Quantum chemistry; semiconductor